2014
DOI: 10.1371/journal.pgen.1004106
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Distortion Affecting Human Noncrossover but Not Crossover Recombination: A Hidden Source of Meiotic Drive

Abstract: Meiotic recombination ensures the correct segregation of homologous chromosomes during gamete formation and contributes to DNA diversity through both large-scale reciprocal crossovers and very localised gene conversion events, also known as noncrossovers. Considerable progress has been made in understanding factors such as PRDM9 and SNP variants that influence the initiation of recombination at human hotspots but very little is known about factors acting downstream. To address this, we simultaneously analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
75
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 52 publications
10
75
2
Order By: Relevance
“…35 and 36 and references in ref. 37), or gene conversion favoring GC-alleles, leading to gBGC (15). Patterns seen in our data ( Fig.…”
Section: Significancesupporting
confidence: 71%
“…35 and 36 and references in ref. 37), or gene conversion favoring GC-alleles, leading to gBGC (15). Patterns seen in our data ( Fig.…”
Section: Significancesupporting
confidence: 71%
“…Comparable estimates have been obtained based on sperm genotyping 6,7 (not genomewide) and coalescent inferences 14,15,25 . Our genomewide estimate of G is 9.5/Mb/generation in the chip dataset (unadjusted for SNP ascertainment) and 5.9/Mb/generation in the sequencing dataset (cf.…”
Section: Resultsmentioning
confidence: 99%
“…Crossover events, which arise through the resolution of the double Holliday junction (dHj) 4 , are also frequently accompanied by gene conversions, hereafter referred to as CO gene conversions. NCO gene conversions most commonly arise via the synthesis-dependent strand annealing (SDSA) pathway 5 , generating short regions of unidirectional homologous exchange 6,7 , but the resolution of the dHj can also lead to NCO gene conversions 8,9 . A schematic overview of these DSB repair mechanisms is given in Supplementary Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Gene conversion is biased in favor of transmission of GC alleles in many eukaryotes (Duret and Galtier 2009). Such a bias has been observed directly in noncrossover (Odenthal-Hesse et al 2014) and crossover (Arbeithuber et al 2015) recombination products in human sperm and can explain patterns of GC content enrichment at mouse hot spots (Clement and Arndt 2013). Accordingly, we found that, in males, noncrossovers frequently showed significant bias, resulting in more conversion to GC than to AT (Supplemental Table S2).…”
Section: Biased Gene Conversion In Noncrossoversmentioning
confidence: 53%